Recent Advances on Pickering Emulsions Stabilized by Diverse Edible Particles: Stability Mechanism and Applications - Li, Wei; Jiao, Bo; Li, Sisheng; Faisal, Shah; Shi, Aimin; Fu, Weiming; Chen, Yiying; Wang, Qiang (Frontiers in Nutrition, 2022)
Pickering emulsions, which are stabilized by particles, have gained considerable attention recently because of their extreme stability and functionality. A food-grade particle is preferred by the food or pharmaceutical industries because of its noteworthy natural benefits (renewable resources, ease of preparation, excellent biocompatibility, and unique interfacial properties). Different food-grade particles are reported by recent publications with distinct shapes resulting from the inherent properties of raw materials and fabrication methods. Furthermore, they possess distinct interfacial properties and functionalities. The review provides a comprehensive overview of the recent advances in the stabilization of Pickering emulsions using diverse food-grade particles, as well as their possible applications in the food industry.